2021
DOI: 10.33824/pjpr.2021.36.3.25
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Internet Gaming Disorder on Self-Appraisal Among University Students: Moderating Role of Gender

Abstract: The objective of the current study was to assess the impact of internet gaming disorder on self-appraisal. Moreover, role of gender as a moderator on the relationship between internet gaming disorder and self-appraisal among university students was also explored. A sample of 300 students was collected through purposive sampling technique, from different universities of Islamabad and Rawalpindi. The participant’s age range was 18-28 years. Self-report measures i.e., Internet Gaming Disorder Scale-short form (Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
0
1
0
Order By: Relevance
“…Additional risk factors for IGD were identified including being younger and male. A recent study by Rasheed et al (2022) found that characteristics including selfevaluation and gender, namely being male, can predict the susceptibility to IGD among Pakistani adolescents. According to Stevens et al (2019) Literature also supported the findings as numerous studies revealed that children of all ages are at a risk of addiction to video games and it is likely to have a negative impact on a child's academic performance.…”
Section: Resultsmentioning
confidence: 99%
“…Additional risk factors for IGD were identified including being younger and male. A recent study by Rasheed et al (2022) found that characteristics including selfevaluation and gender, namely being male, can predict the susceptibility to IGD among Pakistani adolescents. According to Stevens et al (2019) Literature also supported the findings as numerous studies revealed that children of all ages are at a risk of addiction to video games and it is likely to have a negative impact on a child's academic performance.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies identified some risk factors for IGD. The male gender significantly contributed to IGD occurrence, and IGD was even called an emergent health issue for men ( Al Asqah et al, 2020 ; Borges et al., 2019 ; Chen et al, 2018 ; De Pasquale et al, 2018 ; Macur & Pontes, 2021 ; Qin et al, 2020 ; Rasheed et al, 2021 ; Severo et al., 2020 ). Increased gaming time was mentioned as a predisposition factor for IGD ( Jeong et al., 2021 ; Rho et al, 2017 ; Severo et al, 2020 ).…”
Section: Review Of Literaturementioning
confidence: 99%